Role of Red Blood Cells in the Early Stages of Platelet Activation by Collagen - Teresa Santos, M; Vallés, Juana; Aznar, Justo; Luis Pérez-Requejo, J (Thrombosis and Haemostasis, 1986)
Red blood cells (RBC) increase the proaggregatory capacity of a cell-free supernatant obtained by stimulating platelet-rich plasma (PRP) samples with collagen (1 μg/ml) as measured by the BASIC wave; this effect increases with the number of RBC and is proportionally greater with a lower number of platelets or when lower collagen concentrations are used.Aspirin (ASA) modifies the RBC behaviour in relation to their platelet-collagen interaction. This is demonstrated by the fact that when PRP and RBC obtained from the same subjects before and two hours after the ingestion of ASA (0.5 g) were mixed, it was found that non-AS A-RBC stimulate ASA-PRP, probably through a platelet cyclooxygenase independent pathway; ASA-RBC, however, stimulate non-ASA-PRP, but not ASA-PRP, which suggests that they may need an active platelet cyclooxygenase system for their action. This effect of ASA on RBC is not transient and was also observable 48 h after ASA ingestion. In addition, it was found that ASA-RBC greatly increase the activation of a mixture containing a small proportion of non-ASA-PRP in ASA-PRP, a situation that is expected to be encountered “in vivo” after ASA treatment. This effect of ASA-RBC on platelet activation may help to explain the sometimes contradictory clinical effect of aspirin as an antithrombotic drug.
Keywords: Platelet activation; Erythrocytes; Platelet; Erythrocyte interactions; Aspirin